Anthranilic Acid Inhibitors of Undecaprenyl Pyrophosphate Synthase (UppS), an Essential Enzyme for Bacterial Cell Wall Biosynthesis - Jukič, Marko; Rožman, Kaja; Sova, Matej; Barreteau, Hélène; Gobec, Stanislav (Frontiers in Microbiology, 2019)
We report the successful implementation of virtual screening in the discovery of new inhibitors of undecaprenyl pyrophosphate synthase (UppS) from Escherichia coli. UppS is an essential enzyme in the biosynthesis of bacterial cell wall. It catalyzes the condensation of farnesyl pyrophosphate (FPP) with eight consecutive isopentenyl pyrophosphate units (IPP), in which new cis-double bonds are formed, to generate undecaprenyl pyrophosphate. The latter serves as a lipid carrier for peptidoglycan synthesis, thus representing an important target in the antibacterial drug design. A pharmacophore model was designed on a known bisphosphonate BPH-629 and used to prepare an enriched compound library that was further docked into UppS conformational ensemble generated by molecular dynamics experiment. The docking resulted in three anthranilic acid derivatives with promising inhibitory activity against UppS. Compound 2 displayed high inhibitory potency (IC50 = 25 µM) and good antibacterial activity against E. coli BW25113 ΔtolC strain (MIC = 0.5 µg/mL).